PERHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN PPh PASAL 23 PADA PERUSAHAAN MANUFAKTUR YANG BERADA DI KARAWANG - MOCH. DIDI SETIADI; IMAN AKHADI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to analyze the calculating, deposting, reporting, and recording of Income Tax Article 23, which have been performed by manufacturing company in Karawang. The object of this research is manufacturing company which located in Karawang. This research used descriptive analysis by analyzing suitability data which is found in the company and Income Tax Law No. 36 of 2008 and also the common principle of tax accounting. The result of this research shows that the calculation, depositing, and reporting process which have been performed by company was in line with Income Tax Law No. 36 of 2008, as well the recording process have been performed according to the common principle of tax accounting.